Penanaman Nilai Agama Dan Moral Pada Anak Usia Dini Berdasarkan Pendekatan Psikologi Perkembangan - Ni Luh Drajati Ekaningtyas (Pramana: Jurnal Hasil Penelitian, 2022)
The inculcation of religious and moral values in early childhood refers to a process or way to introduce and accustom early childhood to be able to show praiseworthy behavior, which is in accordance with the teachings of the religion it adheres to and does not contradict the prevailing norms. It needs to be done from an early age so that children will be able to behave and form habits of good behavior. This is important so that the next generation will become a generation who are intelligent and have a commendable character both as religious people and as members of the community. This process must be carried out in accordance with the psychological conditions and stages of child development as described in the early childhood developmental psychology, not according to the wishes of the parents or teachers. It is crucial that children are actively involved in the whole process happily and voluntarily so that the results obtained will be maximized. If the child feels forced or tortured in the process, it is likely that the developmental tasks related to religious and moral aspects will fail to be fulfilled. Therefore, it is important for parents and teachers to master the developmental psychology of early childhood so that they are able to understand the task of religious and moral development in early childhood in order to facilitate the proper stimulation to achieve it.